(untitled) (Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze marketing communication strategies in increasing student enrollment at SMK Mambaul Hisan in Blitar Regency. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The respondents of this study consist of the school principal, teachers, and administrative staff. The results indicate that the implemented marketing communication strategies, both internally through the 4P marketing mix and IMC theory, and externally through engagement with the government, community, and students, have contributed to the annual increase in student enrollment. Despite challenges such as low public interest in pesantren-based schools, supporting factors such as educational innovation and improved facilities have strengthened the effectiveness of these strategies. This study provides implications for the development of more effective and sustainable educational marketing strategies.